SAT0305 ASSOCIATION OF SKIN PSORIASIS WITH CLINICAL AND RADIOGRAPHIC CHARACTERISTICS IN AXIAL SPONDYLOARTHRITIS: RESULTS FROM THE GERMAN SPONDYLOARTHRITIS INCEPTION COHORT. (June 2019) - Protopopov, Mikhail; Proft, Fabian; Sieper, Joachim; Haibel, Hildrun; Rudwaleit, Martin; Poddubnyy, Denis
Abstract : Background: Overlap between psoriasis and axial spondyloarthritis (axSpA) is common, as psoriasis occurs in approximately 10% of patients with axSpA. It has been noted that such an association may result in a particular phenotype of the disease, which has not been extensively investigated so far. Objectives: To analyze the association between skin psoriasis and clinical and radiographic characteristics of axSpA. Methods: Altogether 210 patients with definite axSpA (115 with radiographic and 95 with non-radiographic axSpA) from the German Spondyloarthritis Inception Cohort (GESPIC) were included in the current study. Information on the presence of psoriasis, clinical features, parameters of disease activity, and treatment were collected at baseline and every 6 months thereafter. Radiographs of sacroiliac joints and spine were obtained at baseline and after 2 years of follow-up and were scored by two trained readers according to the conventional grading system of the modified New York criteria (grade 0 to 4 per joint) and mSASSS (score 0-72). Group comparison was performed using Mann-Whitney U-Test for continuous variables and Fisher exact test for binary variables. A logistic regression model was constructed to assess the association of the psoriasis with radiographic progression in the sacroiliac joints and in the spine. Results: Overall, 28 patients (13.3%) with axSpA had skin psoriasis. Patients with psoriasis were less frequently HLA-B27 positive in comparison with patients with no skin symptoms (57.1% and 82, 9% respectively, p=0.004), had more frequently a history of peripheral arthritis (57.1% and 31.9%, p= 0.01), had higher disease activity (BASDAI baseline 5.0 ± 2.2 and 3.8 ± 2.1, respectively, p=0.01) and worse physical function (BASFI at baseline 3.8 ± 2.3 and 2.8 ± 2.3, respectively, p=0.02) ( Table 1 ). They were also more frequently treated with DMARDs (57.1% and 24.7%, respectively, p=0.001). Baseline radiographic characteristics were comparable between the groups. There was no statistically significant difference in rates of radiographic spinal progression and progression of radiographic sacroiliitis in patients with vs. without psoriasis ( Table 2 ). In the multivariable logistic regression analysis, adjusted for the smoking status, sex, NSAID intake, presence of syndesmophytes at baseline and time-averaged ASDAS, skin psoriasis showed no significant association with radiographic spinal progression (OR 2.93, 95% CI 0.81 to 10.58) nor with progression of radiographic sacroiliitis by at least 1 grade (OR 1.98, 95% CI 0.72 to 5.43) Conclusion: Presence of skin psoriasis in patients with axSpA was associated with HLA-B27 negativity, peripheral arthritis, higher disease activity and worse functional status, but had no significant impact on radiographic characteristics of the disease. References: none Acknowledgement: GESPIC has been financially supported by the German Federal Ministry of Education and Research (BMBF). As funding by BMBF was reduced in 2005 and stopped in 2007, complementary financial support has been obtained also from Abbott/Abbvie, Amgen, Centocor, Schering-Plough, and Wyeth. Since 2010 GESPIC is supported by Abbvie. Disclosure of Interests: Mikhail Protopopov: None declared, Fabian Proft Grant/research support from: Novartis, Consultant for: yes but less than 10.000, Paid instructor for: yes but less than 10.000, Speakers bureau: yes but less than 10.000, Joachim Sieper Consultant for: Abbvie, Böhringer Ingelheim, Janssen, Lilly, Merck, Mylan, Novartis, Pfizer, UCB., Speakers bureau: Abbvie, Böhringer Ingelheim, Janssen, Lilly, Merck, Mylan, Novartis, Pfizer, UCB., Hildrun Haibel: None declared, Martin Rudwaleit Consultant for: AbbVie, BMS, Celgene, Janssen, Eli Lilly, MSD, Novartis, Pfizer, Roche, UCB Pharma, Consultant for: AbbVie, BMS, Celgene, Janssen, Eli Lilly, MSD, Novartis, Pfizer, Roche, UCB Pharma, Denis Poddubnyy Grant/research support from: AbbVie, Merck Sharp & Dohme, Novartis, Consultant for: AbbVie, Bristol-Myers Squibb, Janssen, Merck Sharp & Dohme, Novartis, Pfizer, UCB Pharma, Speakers bureau: AbbVie, Bristol-Myers Squibb, Janssen, Merck Sharp & Dohme, Novartis, Pfizer, Roche, UCB Pharma